Spinal Gout: An Unusual Cause of Low Back Pain - Sara Shu; Gregory M. Garrison (SAGE Publishing, 2024)
Low back pain is the most common musculoskeletal complaint accounting for over 30 million visits to primary care physicians annually. Serious pathology is found in less than 1% of these visits. Therefore it is often a challenge to distinguish worrisome findings requiring further workup and treatment from common complaints of pain. Gout is an inflammatory arthritis that most commonly affects the appendicular skeleton. It is characterized by the saturation of uric acid and deposition of monosodium urate crystals in joints and tissues. Spinal involvement is rare and is not typically considered on the differential diagnosis for a patient presenting with acute low back pain. We present such a case of a 35-year-old male who presented with intractable back pain, highlighting the need to recognize signs and symptoms that raise suspicion for spinal gout.